Assessing of mouflon biochemical parameters depending on genders - Pošiváková, Terézia; Hromada , Rudolf; Švajlenka , Jozef; Pošivák , Ján (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
The aim of our study was to evaluate the selected biochemical parameters of mouflon depending on gender. For research were used thirty mouflons of both sexes with approximate age in winter season. Blood samples for biochemical analysis were taken from vena jugularis for determination of selected biochemical parameter. Biochemical indicators were measured using the standard automatic analyser. The results of statistical testing of selected biochemical parameters in the experimental group of animals confirmed differences between the genders and at the selected biochemical parameters.